Peningkatan Kapasitas Kewirausahaan Organisasional Anggota Menuju karangtaruna Mandiri - Rusmana, Dede; Fattah, Fuad Abdul; Hidayat, Rachmad (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Karang Taruna, as mandated by the Indonesian Ministry of Social Affairs Regulation No. 25/2019, is a village-level youth organization for social empowerment. This study aimed to evaluate the effectiveness of an entrepreneurship training for Karang Taruna members in Sumberjo Hamlet, Wonogiri. Methods: A paired pretest–posttest design was applied to 20 participants. The intervention comprised socialization, business planning, basic bookkeeping, and digital marketing. Entrepreneurial knowledge was measured before and after the training and analyzed using a Paired t-test at α = 0.05. Results: The pretest mean was 77.35 (SD = 5.234) and the posttest mean was 84.35 (SD = 9.287); the mean difference (pre minus post) was −7.00 with t(19) = −3.335; p = 0.003; 95% CI [−11.393; −2.607]. The pre–post correlation was 0.263 (p = 0.263), indicating a weak association. These findings confirm a significant knowledge gain following the training. Conclusions: The entrepreneurship training effectively improved participants’ understanding and merits continuation through monthly business clinics and a supportive village-level ecosystem. Keywords: Community Service; Entrepreneurship; Karang Taruna; Paired t-test; Rural Youth; Training.